“Prototipo de una APP para contribuir en el aprendizaje de robótica como parte del proyecto STEM de la Facultad de CIYA” - Ante Guanoquiza, Jorge Gabriel (2024)
Robotics is crucial in STEM education to prepare students in digital and coding skills, which are necessary in a world driven by innovation. Despite efforts, many institutions face infrastructure, budget, and training challenges, the lack of didactic materials and access to hands-on learning platforms hinder the full use of robotics education. The development of a mobile application for primary and secondary students in the Cotopaxi Province is proposed, focused on robotics. This application offers information about robotics and its components; besides, it consists of a block programming environment with three levels of difficulty. The first level will have intuitive visual blocks, the second block in natural language, and the third a high-level programming language. The goal is to develop programming skills in a progressively and adaptively way. For the development of this application, it has been decided to use the Java and JavaScript programming language, as well as the Blockly library for the creation of an interactive and friendly block programming environment. Furthermore, an SQLite database has been integrated to ensure quick and efficient access to educational resources.